Simulating Marine Ecosystem Dynamics and Biogeochemical Cycling With Multiple Plankton Functional Types - Jun Yu; Kristen M. Krumhardt; J. Keith Moore; Robert T. Letscher; Shanlin Wang; Nicola A. Wiseman; Matthew C. Long; Keith Lindsay; Michael Levy; Colleen M. Petrik; Adam C. Martiny (Journal of Advances in Modeling Earth Systems, 2025)
Abstract Current representations of marine ecosystems in Earth System Models are greatly simplified, neglecting key interactions between dynamic food webs, biogeochemistry, and climate change. We use the Marine Biogeochemistry Library code base within the Community Earth System Model 2.2.2 to create an expanded ecosystem model with eight phytoplankton groups and four zooplankton size classes (MARBL‐8P4Z). Incorporating more specific plankton types and size classes has the potential to capture a wider range of possible behaviors of the ecosystem, its complex interactions with biogeochemistry, and its feedback to climate change. It also permits stronger observational constraints, including in situ group‐specific biomass and various observational estimates of plankton community composition. MARBL‐8P4Z broadly captures observed global‐scale patterns in biomass and community composition for both phytoplankton and zooplankton, with a good performance in simulating broad biogeochemistry fields. The model shows comparable spatial patterns and magnitudes to the observed picophytoplankton biomass (Prochlorococcus, Synechococcus, picoeukaryotes), and captures the seasonal cycle of mesozooplankton biomass. Picophytoplankton groups and microzooplankton dominate biomass and production in oligotrophic, subtropical regions, while nano‐phytoplankton, diatoms and the larger zooplankton groups prevail at higher latitudes and within upwelling zones. The model simulates reasonable energy transfer efficiency through the food web, with tight linkages between the phytoplankton community composition, zooplankton grazing, and carbon export, with the potential to link to fisheries models. Thus, MARBL‐8P4Z has the potential to account for key climate‐driven ecological shifts in the plankton that will modify ocean biogeochemistry in the future.